Effect of Substituting Table Sugar with Date Fruit Powder on the Nutritional and Sensorial Properties of Cake - Nisar Ahmed Gichki,; Asadullah Marri,; Nida Shaikh,; Asif Irshad, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Despite the World Health Organization's advice to limit sugar consumption, consumers unwillingly rely on table, refined, or added sugars owing to a lack of suitable alternatives. Date powder (DP) is a potential nutraceutical reservoir that can be an excellent natural sugar or table sugar (TS) replacer. Since Dhaki is one premium date fruit variety, it was utilized in its Tamer stage for developing DP owing to its higher sugar content, shelf-life stability, and low moisture. The date fruit was cleaned, depitted, thermally dehydrated (50±1○C for 2 days), powdered, and utilized as a TS replacer in cakes. A total of four formulations of cake sweeteners were set (i.e., T0 = control/ cake without DP, T1 = 10% DP + 90% TS, T2 = 20% DP + 80% TS, T3 = 30% DP + 70% TS). DP and cake formulations were subjected to assessment as per standard analytical methods. Findings showed that DP had 3.45% moisture, 5.22% protein, 0.78% fat, 6.84% fiber, 5.23% ash, 21.34% carbohydrate, 68.18% reducing sugar, 3.33% non-reducing sugar and 71.51% total sugar with pH value 5.4. The nutritional and sensorial properties of all cake samples (T0-T3) remained statistically different (p < 0.05). Among all samples T3 had significantly higher (p < 0.05) average values for fat (19.03%), protein (15.44%), ash (5.77%), carbohydrate (61.36%), fiber (3.51%), non-reducing sugar (6.85%), energy value (478.47 kcal/100g), color (8.33), texture (8.33), taste (9.0), aroma (8.33), and overall acceptability (8.50) followed by T2, T1, and T0. Findings conclude that increasing DP proportion in cakes not merely improved sweetness but also enhanced their nutritional value (fiber content, energy value, etc.), and sensorial attributes. DP is therefore recommended to be used as one suitable TS replacer in a variety of food products.